2016
DOI: 10.1681/asn.2014121165
|View full text |Cite
|
Sign up to set email alerts
|

ADAMTS13 Endopeptidase Protects against Vascular Endothelial Growth Factor Inhibitor–Induced Thrombotic Microangiopathy

Abstract: Thrombotic microangiopathy (TMA) is a life-threatening condition that affects some, but not all, recipients of vascular endothelial growth factor (VEGF) inhibitors given as part of chemotherapy. TMA is also a complication of preeclampsia, a disease characterized by excess production of the VEGF-scavenging soluble VEGF receptor 1 (soluble fms-like tyrosine kinase 1; sFlt-1). Risk factors for VEGF inhibitor-related TMA remain unknown. We hypothesized that deficiency of the VWF-cleaving ADAMTS13 endopeptidase con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 68 publications
1
14
0
Order By: Relevance
“…8,9 ADAMTS13 is a protease that cleaves large vWf multimers that are released from activated endothelial cells, thereby blocking local platelet aggregation and thrombosis. Erpenbeck et al 6 show that overexpression of sFLT-1 in control mice induced mild manifestations of TMAs, which has been previously reported, whereas a lack of ADAMTS13 resulted in no manifestations of TMAs. However, the combination resulted in a lesion that greatly resembled preeclampsia, with thrombocytopenia, hemolytic anemia, glomerular endotheliosis, and marked proteinuria and hypertension.…”
supporting
confidence: 52%
See 4 more Smart Citations
“…8,9 ADAMTS13 is a protease that cleaves large vWf multimers that are released from activated endothelial cells, thereby blocking local platelet aggregation and thrombosis. Erpenbeck et al 6 show that overexpression of sFLT-1 in control mice induced mild manifestations of TMAs, which has been previously reported, whereas a lack of ADAMTS13 resulted in no manifestations of TMAs. However, the combination resulted in a lesion that greatly resembled preeclampsia, with thrombocytopenia, hemolytic anemia, glomerular endotheliosis, and marked proteinuria and hypertension.…”
supporting
confidence: 52%
“…Although exciting, the study would have been stronger if Erpenbeck et al 6 had shown this synergy in pregnant mice. In addition, Erpenbeck et al 6 showed the synergy in mice that were null for the ADAMTS13 gene, thereby having no ADAMTS13 activity at all.…”
mentioning
confidence: 96%
See 3 more Smart Citations